Comparative seed germination study across alien grapes (Vitis, Vitaceae) in Europe. (14th September 2017) - Orsenigo, S; Ardenghi, N M G; Vagge, I; Cauzzi, P; Müller, J V; Mondoni, A
Summary: Alien grape ( Vitis, Vitaceae) species and recently described hybrids are recognised as major environmental weeds in southern Europe, based on their tendency to spread into natural and semi‐natural habitats, often behaving as invasive species. Despite a high number of agronomic, genetic and phytopathological studies on Vitis cultivars, regeneration from seed has been poorly investigated, although it plays a key role in plant distribution and evolution. To this end, in this study we exposed seeds of eight wild grapes in Europe (three species and five nothospecies, including the native Vitis vinifera ), to different temperature treatments in the laboratory. Fresh seeds from all studied taxa were dormant and germinated only after cold and/or warm plus cold stratification, but showing significant differences between the species. Seeds of V. vinifera showed an intermediate complex morphophysiological dormancy, while all other tested Vitis taxa exhibited a deep complex morphophysiological dormancy. Dark conditions reduced the germination percentage in Vitis labrusca, Vitis riparia and V. vinifera and their hybrids, and alternating temperatures elicited the highest germination percentages in all populations. Our results demonstrated for the first time that Vitis hybrids are capable of regeneration by seed, even in the absence of dispersal by animals. The germination processes studied here help understand the current expansion of alien Vitis taxa in Europe outside the viticultural areas. Consequently, germination requirements contribute to a better understanding of the mechanisms underlying alien Vitis taxa establishment and invasion.